N-acetylcysteine and meso-2,3 dimercaptosuccinic acid alleviate oxidative stress and hepatic dysfunction induced by sodium arsenite in male rats - Abu El-Saad AM; Al-Kahtani MA; Abdel-Moneim AM (Dove Medical Press, 2016)
Ahmed M Abu El-Saad,1,4 Mohammed A Al-Kahtani,2 Ashraf M Abdel-Moneim3,4 1Department of Biology, Faculty of Medicine, Dammam University, Dammam, Saudi Arabia; 2Department of Biology, Faculty of Science, King Khalid University, Abha, Saudi Arabia; 3Department of Biological Sciences, Faculty of Science, King Faisal University, Al-Ahsa, Saudi Arabia; 4Department of Zoology, Faculty of Science, Alexandria University, Alexandria, Egypt Abstract: Environmental exposure to arsenic represents a serious challenge to humans and other animals. The aim of the present study was to test the protective effect of antioxidant N-acetylcysteine (NAC) either individually or in combination with a chelating agent, meso-2,3-dimercaptosuccinic acid (DMSA), against sodium arsenite oral toxicity in male rats. Five groups were used: control; arsenic group (orally administrated in a concentration of 2 mg/kg body weight [b.w.]); the other three groups were orally administrated sodium arsenite in a concentration of 2 mg/kg b.w. followed by either NAC (10 mg/kg b.w., intraperitoneally [i.p.]), DMSA (50 mg/kg b.w., i.p.) or NAC plus DMSA. Arsenic toxicity caused significant rise in serum aspartate aminotransferase, alanine aminotransferase and total bilirubin, and a significant decrease in total protein (TP) and albumin levels after 3 weeks of experimental period. In addition, arsenic-treated rats showed significantly higher arsenic content in liver and significant rise in hepatic malondialdehyde level. By contrast, sharp decreases in glutathione content and catalase and glutathione reductase activities were discernible. NAC and/or DMSA counteracted most of these physiologic and biochemical defects. NAC monotherapy was more effective than DMSA in increasing TP, while DMSA was more effective in decreasing alanine aminotransferase. The combined treatment was superior over monotherapies in recovery of TP and glutathione. Biochemical data were well supported by histopathological and ultrastructural findings. In conclusion, the combination therapy of NAC and DMSA may be an ideal choice against oxidative insult induced by arsenic poisoning. Keywords: arsenic, N-acetylcysteine, meso-2,3-dimercaptosuccinic acid, liver pathology, oxidative imbalance